(untitled) (Bangladesh Journal of Medicine, 2019)
Background: Polyneuropathy has many different causes. It is often very difficult to find out the cause. Nerve conduction study (NCS) can classify neuropathy as axonal and demyelinatig variety and direct the search for cause. Methodology: Purposively selected 80 patients from the department of Neurology Dhaka Medical College during the period of January 2009 to June 2010 were taken for NCS whose were compatible with polyneuropathy by history and clinical examination. Clinical, electrophysiological feature and pattern of polyneuropathy were analyzed. Results: Mean age of the patients was 34.5 ±6.8 and M: F was 1.8:1. Students, laborer and cultivators were the most affected people. 55% patients were acute cases and 35% patients were chronic Cases. 30% patient had no known risk factor for neuropathy 25% patient had antecedent infection, 15% had diabetes mellitus, 7.5% were exposed to drugs/toxins or solvents and 5% had family history of neuropathy. In clinical examination 37.5% patients were in motor type, 10% pure sensory type and 52.5% mixed sensorimotor type. In NCS47.5% were motor, 7.5% pure sensory 45% mixed sensorimotor type. Axonal were 47.5%, demyelinating 27.5% and 25% as mixed axonal and demyelinating type. Conclusion: NCS in polyneuropathy play critical role by classifying it as axonal or demyelinating and shorten the cause. Bangladesh J Medicine Jan 2020; 31(1) : 3-8